2014
DOI: 10.1177/1060028014531737
|View full text |Cite
|
Sign up to set email alerts
|

Colesevelam, Ezetimibe, and Patients With Type 2 Diabetes Mellitus

Abstract: In this health care database analysis among patients with HCh and T2DM, colesevelam was associated with decreased risk of a composite CV event compared with ezetimibe, despite lower persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…After adjustment for any baseline differences, fewer subjects on colesevelam had the primary CV event (HR = 0.58, p = 0.004). However, the authors themselves concluded that change in clinical practice cannot be made based on this study alone due to the limitation of a retrospective design [ 38 ].…”
Section: Available Hypoglycemic Classesmentioning
confidence: 99%
“…After adjustment for any baseline differences, fewer subjects on colesevelam had the primary CV event (HR = 0.58, p = 0.004). However, the authors themselves concluded that change in clinical practice cannot be made based on this study alone due to the limitation of a retrospective design [ 38 ].…”
Section: Available Hypoglycemic Classesmentioning
confidence: 99%